2021
DOI: 10.51470/plantarchives.2021.v21.s1.001
|View full text |Cite
|
Sign up to set email alerts
|

Study the Line X Tester Hybridization, [Ii] Seeds Yield and It's Component in Squash (Cucurbita Pepo L.)

Abstract: The experiment was carried out during growing season (spring 2018) at the field vegetable experiments, department of horticulture and landscape design, college of agriculture and forestry, Mosul University to Study the line x tester hybridization [II] seeds yield and it's component in squash (Cucurbita pepo L.). The experiments materials consisted of 6 genotypes and two varieties as tester of squash plant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The preponderance of nonadditive gene action for various yield and yield attributing traits was probably due to overdominance of genes and such gene action is very useful for the exploitation of heterosis in F1 hybrids. The possibilities for commercial exploitation of heterosis for yield attributes has also been reported by Jasim and Esho [17] in summer squash; Ashwini, B [20] in bitter gourd. However, the differences in the results might have due to the differences in the genetic material studied.…”
Section: Components Of Variancementioning
confidence: 60%
See 1 more Smart Citation
“…The preponderance of nonadditive gene action for various yield and yield attributing traits was probably due to overdominance of genes and such gene action is very useful for the exploitation of heterosis in F1 hybrids. The possibilities for commercial exploitation of heterosis for yield attributes has also been reported by Jasim and Esho [17] in summer squash; Ashwini, B [20] in bitter gourd. However, the differences in the results might have due to the differences in the genetic material studied.…”
Section: Components Of Variancementioning
confidence: 60%
“…The role of additive and dominant genes in the inheritance various traits in bitter gourd was observed by various researchers viz., Bhatt et al [16] for various yield and yield attributes. Jasim and Esho [17] reported that additive variance was responsible for vine length whereas, non-additive for yield in summer squash. Similar results were observed by Talukder et al [18] in bitter gourd.…”
Section: Components Of Variancementioning
confidence: 99%
“…Devi et al (2017a) found both additive and non-additive gene action in snake gourd. Jasim and Esho (2021) reported that additive variance was responsible for vine length whereas, non-additive for yield in summer squash. Similar results were also found in eggplant (Devmore et al, 2016), in bitter gourd (Talukder et al, 2018), in cucumber (Golabadi et al, 2017), and in bottle gourd Quamruzzaman et al (2020) found non-additive gene effects for first female flowering node as well as female flower number per stem, branches per plant in ridge gourd.…”
Section: Resultsmentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License season compared to the early spring season. C. pepo L. is a cross pollinated vegetable crop having a diploid number of chromosomes (2n = 2X = 40) which is cultivated for its fruits to be used in human nutrition (Jasim and Esho, 2021). The sexual development in summer squash is monoecious, occurring in separate locations on the same plant, as well as isolated in the leaf axils.…”
Section: Introductionmentioning
confidence: 99%